PKM Upaya Peningkatan Nilai Tambah Produk Pada Kelompok Wirausaha Yuk Meblanja di Desa Pemecutan Klod - Ida Ayu Surasmi; Ni Made Ayu Gemuh Rasa Astiti; A. A. Ayu Dewi Larantika (Community Service Journal (CSJ), 2024)
Lumut ice is a drink that has long been known, but it is hoped that increasingly advanced developments will not leave this type of drink behind. Likewise, herbal medicine is a traditional Indonesian drink made from herbal plants, such as herbal medicine made from the turmeric plant. One of the business groups that is the object of service is the yuk meblanja business group located in Pemecutan Klod village. This entrepreneurial group is interested in making moss ice drinks and turmeric herbs. Through community service activities, an approach is carried out, there are problems faced, including the beverage products produced are not yet varied, products are made only on the basis of orders and finances are still very simple, they do not have well-organized business and financial bookkeeping records. By using this approach, a solution is provided for Let's go shopping to strengthen the entrepreneurial spirit, better packaging by providing expiration labels and drink ingredients outside the packaging, increasing online and offline marketing, streamlining the production process.